2015
DOI: 10.1007/s00408-015-9776-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression by Sodium Valproate in Epithelial-to-Mesenchymal Transition

Abstract: Histone acetylation was down-regulated by TGF-β1 stimulation in A549 cells. VPA partially inhibited EMT and the decrease of histone acetylation, which plays an important role in the progression of EMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…HDAC inhibitor (HDACi) drugs, romidepsin [155], trichostatin A [156, 157], suberoylanilide hydroxamic acid [123, 158], sodium valproate [159], panobinostat [160, 161], and valproic acid [162, 163], have all been shown to suppress fibrosis. In a standard animal model of cutaneous radiation syndrome, application of topical formulations of phenylbutyrate, an HDACi [164] and oxidative stress inhibitor [165167], reduced acute skin damage and protected from late radiation-induced effects, such as fibrosis and tumor formation [168].…”
Section: Ros-mediated Histone Modification Changes In Rifmentioning
confidence: 99%
“…HDAC inhibitor (HDACi) drugs, romidepsin [155], trichostatin A [156, 157], suberoylanilide hydroxamic acid [123, 158], sodium valproate [159], panobinostat [160, 161], and valproic acid [162, 163], have all been shown to suppress fibrosis. In a standard animal model of cutaneous radiation syndrome, application of topical formulations of phenylbutyrate, an HDACi [164] and oxidative stress inhibitor [165167], reduced acute skin damage and protected from late radiation-induced effects, such as fibrosis and tumor formation [168].…”
Section: Ros-mediated Histone Modification Changes In Rifmentioning
confidence: 99%
“…Other mechanisms may also exist that mediate the VPA-regulated EMT process. Noguchi et al (38) revealed that histone modification correlated with EMT. It is reasonable to make a connection between different media proteins and EMT regulation.…”
Section: Smad4 Expression Tif1-γ Expression -------------------------mentioning
confidence: 99%
“…These results suggested that the process of fibrosis had been initiated in terms of the gene expression profile but not on the histopathological features in early indium lung. The expression of several epithelial or mesenchymal marker genes, such as Cdh1 or Acta2, was not changed suggesting that epithelial-to-mesenchymal transition, a key phenomenon in fibrogenesis (Kalluri & Weinberg, 2009;Noguchi et al, 2015), had not occurred or was undetectable, possibly due to RNA extraction from the whole lung. In histopathology, there were no collagen accumulation characteristics of pulmonary fibrosis, and there were no cholesterol clefts, observed in many human indium lung cases (Cummings et al, 2012), and observed in long-term observation of ITO-or indium oxide-treated hamsters (Tanaka et al, 2010).…”
Section: Discussionmentioning
confidence: 85%